Data Stream Mining between Classical and Modern Applications: A Review - Al Abd Alazeez, Ammar Thaher Yaseen (al-Tarbiyah wa-al-ʻilm lil-ʻulūm al-insānīyah : majallah ʻilmīyah muḥakkamah taṣduru ʻan Kullīyat al-Tarbiyah lil-ʻUlūm al-Insānīyah fī Jāmiʻat al-Mawṣil, 2021)
Data mining (DM) is an amazing developing with incredible chances to advantage institutions centre of main data of information accumulated of conduct their customer and expected customer. DM identified data included in information which questions and summaries cannot viably discover. DM is a straight way to examining data of periodic data records and summing up in useful information - information could be used in expand outputs, reduction costs, or both. DM allows clients to verify data of various measurements or points, classify it, and sum up the connections recognized. There are four types of DM: 1) Classification and regression, 2) Clustering, 3) Association Rule Mining, and 4) Outlier/Anomaly Detection. Tending to the velocity part of Big Data (BD) has as of late pulled in a lot of revenue in the investigation local area because of its critical effect on information from pretty much every area of life like medical services, financial exchange, and interpersonal organizations, and so on. A lot of paper works verified the velocity challenge via stream mining data. The majority of streaming mining data articles centres around adjusting primary classifications of algorithms, methods and techniques of classic information to the modified information circumstance. This research explores widely the latest literature of mining stream data field recognizes the essential ready nodes supporting variance founded methods. This study not simply benefits examiner to make strong assessment subjects and separate gaps in the field yet moreover helps specialists for DM and BD application structure headway.